2020
DOI: 10.1177/1077558720925296
|View full text |Cite
|
Sign up to set email alerts
|

Care Team Perspectives About an Inpatient Portal: Benefits and Challenges of Patients’ Portal Use During Hospitalization

Abstract: While current research about inpatient portals has focused largely on the patient perspective, it is also critical to consider the care team point of view, as support from these individuals is essential to successful portal implementation and use. We held brief in-person interviews with 433 care team members across a six-hospital health system to explore opinions about patients’ use of an inpatient portal as perceived by care team members. Using the Inpatient Portal Evaluation Framework, we characterized benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 34 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Inpatient portals are potentially powerful tools that can empower and engage patients in their health care. 1 2 21 Yet getting portals into the hands of hospitalized patients in a reliable manner remains a challenge for many hospitals. 8 11 12 Our findings suggested that the three strategies of establishing provisioning processes, having persistent unit-level champions, and actively promoting the distribution and use of MCB tablets can make a difference in unit provisioning performance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Inpatient portals are potentially powerful tools that can empower and engage patients in their health care. 1 2 21 Yet getting portals into the hands of hospitalized patients in a reliable manner remains a challenge for many hospitals. 8 11 12 Our findings suggested that the three strategies of establishing provisioning processes, having persistent unit-level champions, and actively promoting the distribution and use of MCB tablets can make a difference in unit provisioning performance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, related research has shown that proxy users, such as spouses and family members, can play a critical role in supporting use of MCB, suggesting that these individuals may be another important group to target for provisioning. 2…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations